The students’ attitudes towards using E- learning in Riyadh’s middle schools - Bin Mubrad, Noura Rashed (Journal of Educational and Psychological Sciences, 2021)
The study aimed to identify students’ attitudes towards using E- learning in Riyadh’s middle schools. The study used the descriptive survey approach to achieve the objectives of the study. The researcher also used the Al- Dhale’i questionnaire (2017) as a study tool, consisting of (20) paragraphs, after making sure of its validity and reliability. The study sample consisted of (150) middle school students in Riyadh, (75) male and (75) female students. The results concluded that the students’ attitudes towards using E- learning in Riyadh’s middle schools is on a moderate degree, with an arithmetic average (2.32). The results also revealed that there were statistically significant differences at the level of significance (α ≤ 0.05) according to the gender variable, and they were in favor of male students, and there were no statistically significant differences at the level of significance (α ≤ 0.05) according to the grade variable. The study came out with a set of recommendations, including the necessity of educating students about the importance of E- learning, as well as encouraging students to use E- learning for their education, also providing the necessary tools in educational environments that allow students to use E- learning.